PeroxiBase a powerful tool to collect and analyse peroxidase sequences from Viridiplantae - Oliva, Michele (Journal of experimental botany, 2009)
Peroxidases are enzymes that are implicated in several biological processes and are detected in all living organisms. The increasing number of sequencing projects and the poor quality of annotation justified the creation of an efficient tool that was suitable for collecting and annotating the huge quantity of data. Started in 2004 to collect only class III peroxidases, PeroxiBase has undergone important updates since then and, currently, the majority of peroxidase sequences from all kingdoms of life is stored in the database. In addition, the web site (http://peroxibase.isb-sib.ch) provides a series of bioinformatics tools and facilities suitable for analysing these stored sequences. In particular, the high number of isoforms in each organism makes phylogenetic studies extremely useful to elucidate the complex evolution of these enzymes, not only within the plant kingdom but also between the different kingdoms. This paper provides a general overview of PeroxiBase, focusing on its tools and the stored data. The main goal is to give researchers some guidelines to extract classified and annotated sequences from the data base in a quick and easy way in order to perform alignments and phylogenetic analysis. The description of the database is accompanied by the updates we have recently carried out in order to improve its completeness and make it more user-friendly